THE EFFECTIVENESS OF FAMILY KNOWLEDGE ABOUT SCHIZOPHRENIA TOWARD FREQUENCY OF RECURRENCE OF SCHIZOPHRENIC FAMILY MEMBERS AT POLY MENTAL GRHASIA MENTAL HOSPITAL D. I. YOGYAKARTA - Istichomah, Istichomah; R, Fatihatur (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2019)
Background: Schizophrenia is a persistent and serious brain disease, which results in psychotic behavior, concrete thinking and difficulties in processing information, interpersonal relationships, and solving problems. The success of mental illness services is influenced by several factors, one of which is the lack of family knowledge about mental disorders. Increasing family knowledge about schizophrenia is important to enable early intervention efforts, because if it is unchecked it will have a bad impact and often experience recurrence. Objective: To find out the relationship between family knowledge level about schizophrenia and frequency of recurrence of schizophrenic family members at Poly Mental Grhasia Mental Hospital D. I. Yogyakarta. Research Methods:This study was an inductive study with quantitative types using cross sectional survey approach method. The population in this study is 310 schizophrenic family members. The sampling technique usedwas accidental sampling with 175 respondents in total. The measuring instrument used a questionnaire regarding family knowledge about schizophrenia. Data analysis was used a Pearson Product Moment correlation with a significance level of 5%. Results: The level of family knowledge about schizophrenia has a Effectiveness toward the recurrence frequency of schizophrenia family members. Analysis test using Pearson Product Moment correlation with the result of Rresult (0.861)> Rtable (0.148), which has a significance level of p<0.05 and the result of p=0.000. Conclusion: There is effectiveness family knowledge about schizophrenia toward the frequency of recurrence of schizophrenic family members at the Poly Mental Grhasia Mental Hospital D. I. Yogyakarta. Suggestion :The schizophrenic family members are expected to improve their knowledge regarding schizophrenia to allow early intervention efforts, so that the recurrence frequency of schizophrenic family members can be minimalized.